2005
DOI: 10.1093/nar/gki205
|View full text |Cite
|
Sign up to set email alerts
|

A graphical simulation model of the entire DNA process associated with the analysis of short tandem repeat loci

Abstract: The use of expert systems to interpret short tandem repeat DNA profiles in forensic, medical and ancient DNA applications is becoming increasingly prevalent as high-throughput analytical systems generate large amounts of data that are time-consuming to process. With special reference to low copy number (LCN) applications, we use a graphical model to simulate stochastic variation associated with the entire DNA process starting with extraction of sample, followed by the processing associated with the preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 33 publications
3
88
0
Order By: Relevance
“…The allele will not be selected and hence drop out when N = 0, which happens with probability P (N = 0) = (1 − π e π a ) n 0 . Gill et al (2005) estimated π e = 0.6 and π a = 20/66 for their laboratory procedures, giving π e π a = 0.182, and hence a dropout of 0.818 n 0 ≈ exp(−0.2n 0 ).…”
Section: Dropoutmentioning
confidence: 98%
See 4 more Smart Citations
“…The allele will not be selected and hence drop out when N = 0, which happens with probability P (N = 0) = (1 − π e π a ) n 0 . Gill et al (2005) estimated π e = 0.6 and π a = 20/66 for their laboratory procedures, giving π e π a = 0.182, and hence a dropout of 0.818 n 0 ≈ exp(−0.2n 0 ).…”
Section: Dropoutmentioning
confidence: 98%
“…Recently, Cowell (2009) has carried out an analysis of the validity of the gamma model by comparing with simulations of mixtures using a stochastic procedure presented by Gill et al (2005). He found that the gamma model gives a good description of the distribution of peak area values arising from the PCR process in amplifying moderate to large quantities of (simulated) DNA, but becomes inadequate in the low-copy-template regime where dropout becomes a significant factor.…”
Section: Gamma Modelmentioning
confidence: 99%
See 3 more Smart Citations